The Great Sleepy-Time Stew Rescue - Mills, Charles; Nang Chan Yeema (Nampa, Idaho, United States Pacific Press Publishing Association, 2004)
When eleven-year-old Alex works on his cooking honor badge, he and his Pathfinder Club friends try to help a homeless family and become involved in an unexpected adventure.
Keywords: Adult Fiction